Network analyses–based identification of circular ribonucleic acid–related pathways in intrahepatic cholangiocarcinoma - Anuradha Moirangthem; Xue Wang; Irene K Yan; Tushar Patel (Tumor Biology)
Circular ribonucleic acids are non-coding ribonucleic acids that can be identified from genome sequencing studies. Although they can be readily detected, their regulation and functional role in human diseases such as cancer are unknown. Using a systematic approach, we analyzed ribonucleic acid-sequencing data from a well-characterized cohort of intrahepatic cholangiocarcinoma to identify genetic pathways related to circular ribonucleic acids. Although the expression of most circular ribonucleic acids was similar in both the cancer and non-cancer tissues, expression of circ2174 was significantly increased in cancer tissues. Network analysis of co-related genes identified several pathways associated with circ2174, and common regulatory mediators between genes in these pathways and circ2174. Among these, alterations in several genes involved in interleukin-16 signaling responses such Lck, interleukin-16, and macrophage inflammatory protein-1-beta were the most prominent. Octamer transcription factor (Oct)-2 was identified as a signal transducer that was common to both circ2174 and interleukin-16. Circ2174 has sequence complementarity to miR149 which can target Oct-2. These data suggest a mechanism whereby circ2174 can act as a sponge to regulate the expression of miR149, and thereby modulate Oct-2 and interleukin-16 signaling pathways in cholangiocarcinoma.